2010
DOI: 10.1097/brs.0b013e3181bb1bf2
|View full text |Cite
|
Sign up to set email alerts
|

Colon Perforation Caused by Migration of a Bone Graft Following a Posterior Lumbosacral Interbody Fusion Operation

Abstract: We have presented a case whose migrated L4-S1 femur graft led to perforation of the cecum. We recommend that frequent radiologic follow-up should be done in patients at risk to show complications early enough to avert severe consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In one publication, bowel injury occurred during sacrectomy for tumor removal (34). There were 10 publications in which bowel injury was described after lateral approaches and MIS spinal procedures in the lumbar spine (11,12,(14)(15)(16)21,23,24,27,33). Additionally, one study reported bowel injury after instrumentation failure in a procedure for a spinal deformity (25).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one publication, bowel injury occurred during sacrectomy for tumor removal (34). There were 10 publications in which bowel injury was described after lateral approaches and MIS spinal procedures in the lumbar spine (11,12,(14)(15)(16)21,23,24,27,33). Additionally, one study reported bowel injury after instrumentation failure in a procedure for a spinal deformity (25).…”
Section: Resultsmentioning
confidence: 99%
“…The surgical procedures involved in the bowel injuries were discectomy (13,17,18,26,(30)(31)(32), microdiscectomy (19,20,22,28,29) extreme lateral interbody fusion (XLIF) (11), AxiaLIF (14,15,23,24,33), ALIF (12,21), anterior endoscopic spondylodesis at L5-S1 (27) posterior lumbar interbody fusion (PLIF) (16), posterior spinal fusion-anterior spine release through a retroperitoneal approach (25), and sacrectomy (34). An analysis of the types of surgeries that these patients underwent demonstrated that bowel injury was more frequent in lumbar discectomy and microdiscectomy (18 of 31 patients, 58.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dislocation may occur posteriorly into the spinal canal [11]. In case of anterior dislocation, the vessels, visceral structures, or nerves may be involved [12,13]. In the case described above, the anterior dislocation of the spacer caused arrosion of the sigmoid colon with perforation and transanal passage of the spacer.…”
Section: S290mentioning
confidence: 99%